Functionality of insulin plant (Costus igneus) leaf extracts - Trapse, M. J. L.; Solomon, J. R.; Jacob, J. K. S. (International Journal of Agricultural Technology, 2021)
Costus igneus, a native of South and Central America, is commonly known as the insulin plant that belongs to family Costaceae. This plant is a perennial, upright, and spreading, growing to a height of two (2) feet with the tallest stems falling and lying on the ground. Studies claim that consumption of its leaves lowers blood glucose levels. Results showed that seven out of nine active phytochemical compounds tested was present in C. igneus ethanolic leaf extracts, namely: tannins, saponins, cardiac glycosides, steroids, flavonoids, terpenoids, and alkaloids. Disc diffusion assay revealed that the ethanol extract has exhibited a 20.73 mm and 20.86 mm zones of inhibition against E. coli and S. aureus respectively. Furthermore, LC50 of 2.88 was observed in lethality assay after 24 hours using probit analysis. Based on these observations, the ethanolic extracts of C. igneus contains active biochemical compounds that contributes to its potentiality as antibacterial agent against common food-borne bacteria and can be further studied as anticancer agent due to its high levels of toxicity against A. salina.